A Practical Review on the Application of Constraint Handling Strategies in Evolutionary Computation from an Engineering Point of View - Yousefi, M.; Hooshyar, D.; Ahmad, R.; Darus, A.N. (Praise Worthy Prize S.r.l, 2015)
This study presents a review of the current constraint handling strategies that are being employed in evolutionary computation. The strategies can be as simple as a reject strategy or as sophisticated as decoding or multi-objective approaches. In this study, however, only the prominent methods and previous works are considered. The Evolutionary algorithms cannot handle the constraints by themselves, and the growing application of EAs in various fields of engineering and science, which are mostly highly constrained, has made the use of efficient, easyto- implement and comprehensive constraint handling strategies inevitable. This study will shed light on this field of research and a comparison of various strategies will be also provided.